A prospective association between dietary folate intake and type 2 diabetes risk among Korean adults aged 40 years or older: the Korean Multi-Rural Communities Cohort (MRCohort) Study. Issue 12 (4th December 2017) - Hong, Sang M.; Woo, Hey W.; Kim, Mi K.; Kim, Se Y.; Lee, Young-Hoon; Shin, Dong H.; Shin, Min-Ho; Chun, Byung-Yeol; Choi, Bo Y.
Abstract: It has not been well established whether dietary folate intake reduces the risk of diabetes development. We aimed to clarify the prospective association between dietary folate intake and type 2 diabetes (T2D) risk among 7333 Korean adults aged 40 years or older who were included in the Multi-Rural Communities Cohort. Dietary folate intake was estimated from all 106 food items listed on a FFQ, not including folate intake from supplements. Two different measurements of dietary folate intake were used: the baseline consumption and the average consumption from baseline until just before the end of follow-up. The association between folate intake and T2D risk was determined through a modified Poisson regression model with a robust error estimator controlling for potential confounders. For 29 745 person years, 319 cases of diabetes were ascertained. In multivariable analyses, dietary folate intake was inversely associated with risk of T2D for women, not for men. For women, the incidence rate ratio of diabetes in the third tertile compared with the first tertile was 0·57 (95 % CI 0·38–0·87, P for trend =0·0085) in the baseline consumption model and 0·64 (95 % CI 0·43–0·95, P for trend =0·0244) in the average consumption model. These inverse associations was found in both normal fasting blood glucose group and impaired fasting glucose group among women. Among non-users of multinutrients and vitamin supplements, the significant inverse association remained. Thus, higher dietary intake of folate is prospectively associated with lower risk of diabetes for women.